Factors Associated with Time Spent Performing Housework/Childcare by Fathers of Children Aged Under 12 Years: A Cross-Sectional Study in Japan - Rina Matsubara; Naoko Hikita; Megumi Haruna; Emi Sasagawa; Kaori Yonezawa; Yumi Maeda; Yuka Ikeda (JMIR Publications, 2020)
Objective: The objective of this study is to determine the factors associated with time spent performing housework/childcare by fathers of children under 12 years of age (preschool and elementary school children) in Japan. Methods: An online survey of employees and employers was conducted in 2017. Of the 7,796 total responses to the survey, those of 621 fathers of children aged 0-12 years were analyzed. Participants were divided into two groups: fathers of children aged 0-6 years, and fathers of children aged 7-12 years. Multiple logistic regression analysis was performed on the items for which there was a significant intergroup difference, setting time spent performing housework as the dependent variable and the survey items as the independent variables. Results: For fathers of children aged 0-6 years, working 40 hours or less per week and commuting for one hour or less were associated with more time spent performing housework/childcare. For fathers of children aged 7-12 years, working less than 40 hours a week, working from home more than once a week, and having spouses with full-time jobs were associated with more time spent performing housework/childcare. Conclusion: This study revealed the factors associated with the time spent by fathers of children under 12 in performing housework/childcare. As several of these factors cannot be altered by the fathers' efforts alone, companies and society in general must endeavor to improve work styles to better suit the habits and preferences of fathers. This will promote work-life balance and create better family relationships.